Unprecedented Association: Bilateral UPJ obstruction with grade 3 hydronephrosis caused by Type 2 circumcaval right ureter and left lower pole crossing vessels - Mohammed Salah E. Khalifa Salem; Abdul Alherek; Daniel DaSilva; Jacob Varghese; Alain Mwamba Mukendi (Urology Case Reports)
Bilateral ureteropelvic junction obstruction resulting from distinct vascular anomalies on each side, with a pre-ureteric vena cava on the right and crossing vessels on the left, has not been previously documented in the literature. Even more intriguing is the association between a grade 3 hydronephrosis and a type 2 circumcaval ureter. This unprecedented report discusses this association and its management.